Reliability of N-terminal proBNP assay in diagnosis of left ventricular systolic dysfunction within representative and high risk populations. - Hobbs, F; Davis, R; Roalfe, A; Hare, R; Davies, M (2004)
OBJECTIVE: To determine the performance of a new NT-proBNP assay in comparison with brain natriuretic peptide (BNP) in identifying left ventricular systolic dysfunction (LVSD) in randomly selected community populations. METHODS: Blood samples were taken prospectively in the community from 591 randomly sampled individuals over the age of 45 years, stratified for age and socioeconomic status and divided into four cohorts (general population; clinically diagnosed heart failure; patients on diuretics; and patients deemed at high risk of heart failure). Definite heart failure (left ventricular ejection fraction (LVEF) < 40%) was identified in 33 people. Samples were handled as though in routine clinical practice. The laboratories undertaking the assays were blinded. RESULTS: Using NT-proBNP to diagnose LVEF < 40% in the general population, a level of > 40 pmol/l had 80% sensitivity, 73% specificity, 5% positive predictive value (PPV), 100% negative predictive value (NPV), and an area under the receiver-operator characteristic curve (AUC) of 76% (95% confidence interval (CI) 46% to 100%). For BNP to diagnose LVSD, a cut off level of > 33 pmol/l had 80% sensitivity, 88% specificity, 10% PPV, 100% NPV, and AUC of 88% (95% CI 75% to 100%). Similar NPVs were found for patients randomly screened from the three other populations. CONCLUSIONS: Both NT-proBNP and BNP have value in diagnosing LVSD in a community setting, with similar sensitivities and specificities. Using a high cut off for positivity will confirm the diagnosis of LVSD but will miss cases. At lower cut off values, positive results will require cardiac imaging to confirm LVSD.